Evaluation of interactive effects between paternal alcohol consumption and paternal socioeconomic status and environmental exposures on congenital heart defects. Issue 16 (21st July 2020) - Nie, Zhiqiang; Qu, Yanji; Han, Fengzhen; Bell, Erin M.; Zhuang, Jian; Chen, Jimei; François, Melissa; Lipton, Emily; Matale, Rosemary; Cui, Weilun; Liang, Qianhong; Lu, Xiangzhang; et al.
Abstract: Background: While the maternal risk factors on congenital heart defects (CHDs) have often been assessed, paternal contribution to CHDs, especially the joint effects of paternal risk factors on CHDs remain unknown. This study examined the major impacts of paternal alcohol consumption and its interaction (on multiplicative and additive scales) with paternal socioeconomic status (SES) and environmental exposures on CHDs in China. Methods: A population‐based case–control study involving 4, 726 singleton CHDs cases and 4, 726 controls (without any malformation and matched on hospital, gender, and gestational age) was conducted in Guangdong, China, 2004–2014. Information on parental demographics, behavioral patterns, disease/medication, and environmental exposures (3 months before pregnancy) was collected through face‐to‐face interviews. Conditional logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) while controlling for all parental factors. Results: Paternal alcohol consumption was associated with an increased OR of CHDs (adjusted OR = 2.87, 95% CI: 2.25–3.65). Additionally, paternal smoking, industry occupation, organic solvent contact, virus infection and antibiotic use, living in rural areas, low household income, and migrant status were significantly associated with CHDs (ORs ranged: 1.42–4.44). Significant additive or multiplicative interactions were observed between paternal alcohol consumption and paternal smoking, industrial occupation, and low income on any CHDs (interaction contrast ratio [ICR] = 4.72, 95% CI: 0.96–8.47] and septal defects (ICRs ranged from 2.04 to 2.79, p < .05). Conclusions: Paternal alcohol consumption and multiple paternal factors were significantly associated with CHDs in China. Paternal smoking and low SES factors modified paternal alcohol consumption–CHDs relationships. Further studies are needed to confirm these findings. Abstract :